2014
DOI: 10.1080/10402381.2013.878008
|View full text |Cite
|
Sign up to set email alerts
|

Plant colonization and soil properties on newly exposed shoreline during drawdown of Lake Mead, Mojave Desert

Abstract: Drawdown of Lake Mead from 1998 to 2011 reduced the lake's perimeter by more than 400 km while exposing more than 25,000 ha of formerly submerged land. To evaluate primary plant succession and soil properties in this new shoreline habitat, we sampled surfaces last submerged 3, 6, 9, or 13 years before sampling (including a neversubmerged control) using 150, 100 m 2 plots at 3 sites varying in topography and soil parent material. Consistent with previous research, abundance of the exotic saltcedar (Tamarix ramo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, weed invasion may be short lived; over time, some important native species may colonize weedy sites that are not reinundated (Engel et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…However, weed invasion may be short lived; over time, some important native species may colonize weedy sites that are not reinundated (Engel et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…However, some population sites support minimal biocrust cover (Megill et al 2011), and studies have not found a direct relationship between cryptogamic cover and A. californica distribution (Bangle et al 2010, Megill et al 2011. Arctomecon californica plants have even been observed growing in disturbed spots (hoof prints) within heavily crusted areas (Bangle et al 2010), on topsoil piles awaiting reclamation (Cayenne Engel, Nevada Division of Forestry; Lara Kobelt, BLM, Southern Nevada District Office, personal communications), and at sites previously inundated by Lake Mead (Engel et al 2014). Arctomecon californica seedlings also established sporadically during 2003-2006 along an unimproved road at Lake Mead National Recreation Area along sections where deep soil compaction was alleviated with heavy machinery during late fall 2002 (U.S. Geological Survey unpublished data).…”
Section: Seedling Recruitmentmentioning
confidence: 99%